2021
DOI: 10.3390/compounds1030011
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Role of Oct-1-en-3-ol in Marine Algae

Abstract: Oct-1-en-3-ol has been studied among oxylipins as a global metabolome that induce the defense of marine algae. The present short review summarized the research of oct-1-en-3-ol as the stress response molecule in marine algae including different aspects: (i) its biosynthesis from fatty acids; (ii) its distribution in marine algae; (iii) a direct effect of oct-1-en-3-ol on microorganisms infecting the thalli; (iv) an indirect communication molecule for alga-alga signaling; and (v) as an inducer that initiates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…The short-chain alcohols ethanol, hexan-1-ol, octan-1-ol, and oct-1-en-3-ol were the most abundant (Tables 1 and 2). Previous studies showed that the oxylipin oct-1-en-3-ol is a defence compound in marine algae [18][19][20].…”
Section: Headspace Volatilome Variations Of C Spongiosusmentioning
confidence: 99%
“…The short-chain alcohols ethanol, hexan-1-ol, octan-1-ol, and oct-1-en-3-ol were the most abundant (Tables 1 and 2). Previous studies showed that the oxylipin oct-1-en-3-ol is a defence compound in marine algae [18][19][20].…”
Section: Headspace Volatilome Variations Of C Spongiosusmentioning
confidence: 99%
“…Aliphatic compounds were dominant in both HS-FrPF (56.24 %, f1; 66.00 %, f2) and HS-DrPF (65.16 %, f1; 37.38 %, f2) (Figure 1) samples analysed with both fibres with octan-3-one (HS-FrPF, f1) and heptadecane (HS-FrPF, f2; HS-DrPF, both fibres) as two most abundant compounds (Figure 2). Octan-3-one, fatty acid derivative known as C 8-oxylipin, [15] was identified only in HS-FrPF (24.02 %, f1; 15.39 %, f2). This compound was not detected after airdrying probably because of its high volatility.…”
Section: Headspace Composition Of Vocs Isolated By Hs-spmementioning
confidence: 99%
“…In both samples, the group of aliphatic compounds predominated with 44.99 % in HD-FrPF and 36.67 % in HD-DrPF (Figure 3). Oct-1-en-3-ol, oxylipin known as global metabolome that induces the defence of marine invertebrates and algae, [15] had the greatest abundance in HD-FrPF. It decreased 30.1 times after drying probably because of its high volatility (Figure 4).…”
Section: Composition Of the Vocs Obtained By Hydrodistillationmentioning
confidence: 99%